The management of cover plant residues for cotton cropped in a no-tillage system - Furlani Júnior, Enes [UNESP]; Neves, Danilo De Carvalho [UNESP]; Santos, Marcio Lustosa; Ferrari, Samuel [UNESP] (Editora da Universidade Estadual de Maringá (EDUEM), 2013)
The cutting of plant residue in no-tillage systems under certain environmental conditions becomes necessary to adequately establish and grow crops. This study aims to assess the effect on the yield of different methods of managing millet plant residue in cotton plantations. The study was conducted during the agricultural years 2006/07 and 2007/08, and the treatments included no-mechanical-treatment tillage and the use of a rotary shredder, crimper-roller, and mechanical disintegrator for millet plants before sowing the cotton. Evaluations were performed for the residue fragmentation, emergence speed, percent of soil cover during the cycle and yield of the cotton crop. The emergence speed was faster in the management with the rotary shredder. In 2006/07, the no-tillage treatment showed a rate of loss for soil cover that was 46 percent greater than the disintegrator treatment. The rotary shredder and the disintegrator yielded greater soil coverage during the cultivation cycle, and the yield was highly correlated with the soil cover at 75 days after emergence. The management of the millet residue affected the cotton plants for the two-year study period.

O manejo dos resíduos vegetais em sistema plantio direto em certas condições torna-se necessário para o bom estabelecimento e crescimento da cultura. Este estudo visa verificar o efeito de diferentes formas de manejo de resíduos vegetais de milheto na semeadura e produtividade do algodoeiro. Foi conduzido durante os anos agrícolas 2006/07 e 2007/08, sendo que os tratamentos utilizados foram: sem corte mecânico da fitomassa do milheto, uso de roçadora, rolo faca e desintegrador mecânico em plantas de milheto previamentes semeadas na área experimental e antes da semeadura do algodão. Foram efetuadas avaliações de fragmentação dos resíduos, velocidade de emergência, porcentagem de cobertura do solo durante o ciclo e produtividade da cultura do algodão. A velocidade de emergência foi mais rápida no manejo com roçadora. O tratamento sem corte mecânico apresentou uma taxa de perda de cobertura do solo de 46% maior do que o desintegrador em 2006/07. A roçadora e o desintegrador resultaram numa maior cobertura do solo durante o ciclo de cultivo. O rendimento do algodoeiro foi fortemente correlacionado com a cobertura do solo aos 75 dias após a emergência. O manejo dos resíduos do milheto afetou o rendimento do algodoeiro nos dois anos avaliados.
Manejo da fitomassa da planta de cobertura para semeadura do algodoeiro em sistema plantio direto
Keywords: cobertura do solo; Gossypium hirsutum; Pennisetum glaucum; soil cover; Gossypium hirsutum; Pennisetum glaucum